Patriarchy, male sexuality, oedipal conflict and female subject in K.S. Maniam's the cord - Wan Roselezam bt. Wan Yahya (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
This paper is a feminist reading of K.S. Maniam's play The Cord using the psychoanalytical concepts of patriarchy, male sexuality and oedipal conflict. By reading The Cord against the traditional grain to examine the images of the women (female subject), the three female characters are seen to be active agents although the male characters overpower them in the play. Maniam, though hardly a feminist himself, portrays the three female characters rebelling against the patriarchal norms that restrict them and each takes a different approach to liberate herself from the oppression. For Lakshmi, death is the only way out of misery; for Leela, the struggle for independence still remains an inspiration; and Kali survives her exposure to male exploitation through her innovative self-sufficiency and strength. While the male's integrity and selfrespect appear totally eroded by the experience of self-distrust and self-devaluation, the female's resilience enables her to regain command of her own fate.